Statelessness in Protracted Refugee Situations: Former Angolan and Rwandan Refugees in Zambia - Muchindu, Mazuba (African Human Mobility Review, 2023)
Among migrant populations, refugees form one group that is at high risk of becoming stateless. As those responsible for their wellbeing seek to find durable solutions to their plight, identity documents play a critical role. Without proper identity documents, former refugees are at risk of becoming stateless and face many difficulties in accessing various livelihood opportunities including employment, and services such as health care and education. However, acquiring these documents is sometimes wrought with many challenges including administrative, financial and legal challenges. Legal challenges largely arise from the lack of a comprehensive and coordinated approach of how to deal with such cases especially in states that operate outside the UN Conventions on statelessness. Using case studies of former Angolan and Rwandan refugees in Zambia, I argue that in the absence of a clear guiding framework as provided under the UN Conventions provide, former refugees are at risk of becoming stateless even when they are hosted under very hospitable conditions.